Balloon Angioplasty For Native Coarctation of the Aorta in Infants - O. Borodinova; A. Maksymenko; Y. Kuzmenko; A. Kurkevych (Ukrainian Journal of Cardiovascular Surgery, 2016)
The issue about BAA options in neonates and infants with native CoA is controversal due to the higher rate of reinterventions (50–83%) in comparison with alternative surgical method. Evaluation of the effectiveness of balloon angioplasty and the rate of recurrent coarctation in infants depending on the age of patients at the time of operation are performed in the article.The research was performed on the data of 267 consecutive infants who underwent balloon angioplasty for native coarctation at our clinic from January 2007 to December 2014, 116 of these patients were critically ill. The average age of patients was 2,24±2,3 months Hospital mortality rate was 0,7%. Despite good immediate results in 260 patients, risk of reinterventions after BAA in infants is about 57.3%. BAA in infants is radical in 42.7% of cases and allows to postpone cardiac surgery by an average of 88,6±60,7 days. Patients under the age of 2 months have the greatest risk of reinterventions – about 62,3– 64.2% of cases.BAA is a safe and effective method for treatment infants with CoA with good immediate results. BAA is a safe alternative effective method for treatment infants with CoA over 2 months with relatively low level of reinterventions (about 31–39%).